A feasibility study on NoSweat! disposable underarm sweat shields - Dela Pena, Pamela Bianca; Gozalo, Cecile Maris; Ramos, Dareen; Soliman, Nina Cerissa
The launching of the GRDS Company starts off eith a blast by introducing to the Philippine market the NoSweat Disposable Underarm Sweat Shields! NoSweat! is a self-adhesive, disposable apparel shield that absorbs armpit sweat and prevents wetness from passing through the apparel. It protects clothes from stains in the underarm area. It keeps the user fresh, dry, and clean, and prevents embarrassing wetness. A very popular product in foreign countries, like in the United States of America (USA) and the United Kingdom (UK), NoSweat! is the first of its kind in the Philippine islands. The product is a tried-and-tested solution to one of the most dreaded issues in personal hygiene and the concerns of the percentage of the Philippine population suffering from a condition called hyperhidrosis, a condition characterized by excessive sweating in specific parts of their bodies, most commonly, their hands, feet, and underarms. As mentioned, NoSweat! is the first of its kind in the Philippine consumer market. Although the product seems to be very popular in overseas countries, the company has verified through an extensive survey of about 384 respondents that the concept of the product remains to be unknown here in the Philippines, up until the time that the survey was conducted. This "freshness" of product concept in the standpoint of our target market instantly provides the GRDS Company a competitive edge. Furthermore, by the established 'most likely' forecast of the demand for NoSweat!, the business proves to be progressive, as illustrated in the chart on the right. These figures have been estimated through a conservative approach of focusing on the 3% of the population in the National Capital Region (NCR) who suffer from Hyperhidrosis. With the establishment of the product and the brand name in the Philippine market, sales are to increase by at least 0.5% yearly, in the first 5 years of operation. The conservative approach in forecasting provides more opportunities for growth in market share, as long as plans for the promotion of the product remain intensive and successful. The first 2 years of the NoSweat! Disposable Underarm Sweat Shields are 2 years full of promos, enough to capture a fairly sizeable market. The GRDS Company has decided to price a pair of sweat shields at PhP 10. However, as an introductory price for the first 2 years, a PhP 2 markdown will be campaigned as a discount. The GRDS Company is aiming to reach its customers by placing the product in the most visited supermarkets, grocery stores, and other similar establishments in NCR, and strategically shelving them next to underarm care products, such as deodorants and antiperspirants. The strategy gears towards provision. In doing so, the product is guaranteed to achieve an extensive coverage. Likewise, the company recognizes the effectiveness of advertising in TV and print, such as billboards and the various public utility vehicles (PUVs). The company also plans to have appearances in trade shows, exhibits, and live demonstrations and campaign gigs in supermarkets. Campaigns will also be coursed through the Department of Health (DOH) for the promotion of proper hygiene and the responsibility of taking care of one's body. The GRDS Company, as an organization, is composed of 15 personnel. With its mission of promoting proper hygiene by providing the NCR community with the NoSweat! Disposable Underarm Sweat Shields, the product is also able to indirectly effect an increase in the confidence of the Filipino user. The GRDS Company envisions an empowered Filipino people working towards a better future, free from hesitations and the thoughts that limit them from becoming the best person that they can be for their country. The GRDS Company covers the entire production and distribution of NoSweat! The company has a joint venture form of ownership between its 4 founders - de la Pena, Gozalo, Ramos and Soliman. Top-level management responsibilities will be shared among the four partners. Liability as well as shares of profits and loss will also be shared among the four members. The venture will last for 5 years, and the continuation of the project will depend on the success of the business based on the profit that the product is able to generate. The NoSweat! production facility is located in the city of Mandaluyong, with enough proximity to the geographical center of Metro Manila and reasonable distance from the Manila Sea Port. These are the requirements that have been established for the efficient transportation of goods in terms of product distribution and procurement. The proximity to the geographical center of Metro Manila serves the company's objective of covering as many areas for placement. At the same time, the production facility must also be within reasonable distance from the Manila Sea Port for the efficient transportation of the raw materials that the company imports from the countries China and Malaysia. Among the 3 different production process alternatives that have been evaluated, the top management of the GRDS Company has selected the alternative that involves the fabrication of a smaller-scale automated machinery which entails a fabrication cost of PhP 800,000. The production process is illustrated by the flowchart below. A level-production strategy for the first operational year of the GRDS Company results to a production target of 585,500 pads per quarter. Operating for 6 hours in a day and roughly 22 days per month, the production level translates to a production rate of 25 pads per minute. However, in preparation for any level of increase in demand, the fabricated machine can be adjusted up to its design capacity of 80 pads per minute. With an established productive efficiency of 80%, inventory levels of raw materials must be adjusted by the simple computation of dividing the raw material requirements by 0.80. The total project cost of the GRDS Company amounts to PhP 11,328,627.20. To finance the venture, the GRDS Company will acquire Php 5,000,000 from the bank with an 8% interest per annum, and the remaining amount from independent investors in the form of shares of stocks with a par value of PhP 250. This means that 25,600 stocks worth PhP 250 each, and amounting to about PhP 6,400,000, will be issued for the selected production process. Using the simple payback period, the investment of Php 5,500,000 will be recovered in between the company's 2nd and 3rd years of operation. A payback period of 3 years is acceptable and positive in a project venture of this scale. The main thrust of determining the financial feasibility of manufacturing the NoSweat Disposable Underarm Sweat Shields is worth investing in. Upon the rational and financial evaluation of incurring costs in the establishment of the venture, the total project cost was estimated to be approximately Php 12,400,000.00, which accounts buffer amount for contingencies. This amount of investment was proven attainable given various means such as venture capitalists, opening shares to the stock market, mortgages, bank loan, and seeking government support. In conclusion, the financial feasibility of GDRS Company was proven viable given the sales projections and estimated annual costs of the enterprise. The return of investment (ROI) can be attained before the 3rd year of operation ends, thus proving that the project is a viable investment.